Comunicación y narrativa en políticas públicas: el caso de la consulta popular anticorrupción en Colombia (2020)
On August 26, 2018, 11,674,951 Colombians went to the polls and voted in the Anti-Corruption Referendum, an initiative that included seven mandates that sought to confront corruption in the country. Despite not having reached the threshold required by law by less than one percentage point, the Referendum achieved favorable support of 99% of its voters in each of its proposals and, before that, its promoters had collected 4,236,681 citizen signatures, making it the initiative with the greatest citizen support in recent Colombian history. Moreover, it set a milestone as it was the first time a popular consultation was conducted at the national level, despite being a mechanism for citizen participation created after the 1991 Constitution. This paper seeks to analyze what were the narrative elements present in the Anti-Corruption Referendum and how were they used by the promoters of the campaign to mobilize citizens? The research uses as reference the Narrative Framework for Public Policy proposed by Jones and McBeth. From this analysis, one can identify that the Referendum built a narrative around four essential elements: heroes, villains, victims, and a moral of the story or political solution. Each of these elements was used with greater or lesser intensity, depending on the scenario in which this initiative was presented. In addition, specific villains were created for each of the mandates proposed by the Referendum. Over and above empirical evidence, the emotional elements generated by corruption were used to support their arguments. This paper explores the relevance of communication and narrative in the public policy process and the contributions that these fields can provide for its analysis.